2017
DOI: 10.1111/roiw.12286
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Inequality by Asset Indices: A General Approach with Application to South Africa

Abstract: Asset indices are widely used, particularly in the analysis of Demographic and Health Surveys, where they have been routinely constructed as "wealth indices." Such indices have been externally validated in a number of contexts. Nevertheless, we show that they often fail an internal validity test, that is, ranking individuals with "rural" assets below individuals with no assets at all. We consider from first principles what sort of indexes might make sense, given the predominantly dummy variable nature of asset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 16 publications
4
75
0
1
Order By: Relevance
“…This method was recreated in China and evaluated ecologically against known consumption inequality, appearing to track the same pattern of rising inequality through the 1990s until a peak was reached around 2000, suggesting broadly shared growth and an eventual decline in urban and rural wealth inequality (Ward 2014). A more recent application in South Africa found wealth index inequality fell from a Gini coefficient of 0.47 to 0.29 from 1993 to 2008, but cautions that the use of a negatively loaded first eigenvalue in the calculation of wealth index inequality could lead to this method performing poorly (Wittenberg and Leibbrandt 2017). Although there is clearly more research to be done on the limitations of wealth index inequality, this is an area of research which could grow rapidly given the increasing public interest on this topic.…”
Section: Future Applicationsmentioning
confidence: 88%
See 1 more Smart Citation
“…This method was recreated in China and evaluated ecologically against known consumption inequality, appearing to track the same pattern of rising inequality through the 1990s until a peak was reached around 2000, suggesting broadly shared growth and an eventual decline in urban and rural wealth inequality (Ward 2014). A more recent application in South Africa found wealth index inequality fell from a Gini coefficient of 0.47 to 0.29 from 1993 to 2008, but cautions that the use of a negatively loaded first eigenvalue in the calculation of wealth index inequality could lead to this method performing poorly (Wittenberg and Leibbrandt 2017). Although there is clearly more research to be done on the limitations of wealth index inequality, this is an area of research which could grow rapidly given the increasing public interest on this topic.…”
Section: Future Applicationsmentioning
confidence: 88%
“…As one illustrative example, there is a village in Guinea-Bissau where (unlike the rest of the country) portable gas stoves are highly desired, and therefore behave as a normal good, 5 but because that village is relatively poor compared to other villages, the wealth index scoring of gas stoves is negative (Johnston and Abreu 2016). Similarly, owning a common asset will usually imply a negative scoring, which could perversely rank a household as poorer than one lacking the asset at all (Wittenberg and Leibbrandt 2017). Even obtaining reliable information on rural assets is complicated by survey respondents often having difficulty answering questions about the number of hectares of agricultural land owned or even whether they live in an urban or rural area (Chakraborty et al 2016).…”
Section: Urban-rural Considerationsmentioning
confidence: 99%
“…This means that coefficients corresponding to owning a large number of assets may be smaller than those corresponding to owning fewer assets. This lack of monotonicity of the coefficients was also noted by Moser and Felton (2007) and Wittenberg and Leibbrandt (2017) and is a serious problem because the AIs lose discriminating power and their coefficients are hard to interpret.…”
Section: Household Survey Datamentioning
confidence: 79%
“…Not surprisingly, Filmer and Scott () therefore found that AIs were useful for measuring differences of certain welfare indicators but not of others. Wittenberg and Leibbrandt () also argue that AI tend to exaggerate urban–rural differences by undervaluing rural assets (such as livestock), although this is unlikely to apply to our entirely rural sample. Recalling these conceptual difficulties, we now evaluate the different CATPCA AIs computed with respect to the measure of household income available in our data.…”
Section: Estimation Of Asset Indices In Two Rural Provinces In Laos Amentioning
confidence: 88%
“…In some contexts, the correlation between asset indices and consumption is in fact low to moderate at best (Ngo, ), leading some researchers to conclude that they are poor proxies for consumption (Howe et al, ). Thus, when household consumption is the indicator of interest, using asset indices as proxy may induce mistargeting of programs or may generate inaccurate conclusions regarding inequality (Houweling et al, ; Lindelow, ; Wittenberg and Leibbrandt, ).…”
Section: Introductionmentioning
confidence: 99%